Effect of active modified atmospheres on the quality of non-astringent persimmons (Caqui Giombo) D. kaki Thunb. when stored under refrigerated conditions - De Moraes, M. R. [UNESP]; Daiuto, R. [UNESP]; Vietes, R. L. [UNESP]; Cardoso, N. C. [UNESP]; Smith, R. E. (My University, 2013)
The effects of active modified atmospheres were evaluated in ‘Giombo’ persimmons with tannins already removed (non-astringent) and stored at 0°C and 85-90% relative humidity for 35 days. The goal was to maintain quality and delay ripening. The fruits were picked by hand when they were about 50% green, sanitized and subjected to different mixtures of CO2 and O2. Fruits were wrapped in thin film plastic made of nylon + polyethylene and analyzed every seven days for weight loss, respiratory activity, coloration, titratable acidity, soluble solids, ratio, pH, firmness, pectin methyl esterase and polygalacturonase enzyme activities, reducing sugars, ascorbic acid and astringency index. Refrigerated storage and active modified atmospheres were effective in conserving the quality of ‘Giombo’ persimmons. The fruits submitted to the highest CO2 concentrations (7 and 8%) had the lowest weight loss and respiratory intensity with a delay in the climacteric peak.